Peningkatan Kualitas Briket Ampas Kopi Menggunakan Perekat Kulit Jeruk Melalui Metode Torefaksi Terbaik - Qanitah Qanitah; Yurdika Dwi Fatholah Akbar; Zeni Ulma; Yuli Hananto (Journal of Engineering Science and Technology, 2023)
Energy is generally divided into two, the first is non-renewable energy for example oil, coal, and natural gas while the second is renewable energy such as water power, solar power, wind power, and biomass. Briquettes is one of the developments of biomass as an alternative fuel. The purpose of this study was to make and analyze the characteristics of coffee grounds briquettes using an adhesive from orange peel with torrefaction method. Torrefaction is a low temperature (200-300 oC) carbonization process without oxygen. Briquettes are made by percentage of coffee grounds and orange peel adhesive 70% : 30%, 60% : 40%, and 50% : 50%. Torrefaction process with a temperature of 200 oC within 60 minutes without any air or little air in the furnace with the addition of modified elbows. The results showed that the best composition was found in DK1 with a ratio of 70% coffee grounds with 30% orange peel adhesive, which has density 0.49 gr/cm3, water content 5.11%, volatile matter content 78.33%, bound carbon content 17.31%, 0.62% ash content, and 4656 cal/gr calorific value